Alpha-Fetoprotein as a Predictive Marker for Patients with Hepatitis B-Related Acute-on-Chronic Liver Failure - Xiaoping Wang; Caifei Shen; Jianjiang Yang; Xianjun Yang; Sen Qin; Haijun Zeng; Xiaoling Wu; Shanhong Tang; Weizheng Zeng (Canadian Journal of Gastroenterology and Hepatology)
Background and Aims. The value of alpha-fetoprotein (AFP) in hepatitis B-related acute-on-chronic liver failure (HBACLF) is not fully understood. The present study aimed to evaluate the prognostic effect of AFP on the prediction of HBACLF outcomes. Methods. We investigated a cohort of patients with HBACLF admitted from January 2013 to May 2017. The endpoint of followup was 180 days, death, or liver transplantation. AFP concentrations were estimated on admission. To make statistical comparisons, we used chi-squared test, receiver operating characteristic (ROC) curve analysis, survivorship curve analysis, and Cox proportional-hazards model. Results. A total of 92 patients (81.5% male, median age of 46 years) were included. Overall survival rate within 180 days was 43.48%, and the value of log10AFP⁡  ≥ 2.04 indicated a better prognosis with 76.9% specificity and 62.5% sensitivity for patients with HBACLF. Age (HR 1.041), total bilirubin (HR 1.004), log10AFP⁡  (HR 2.155), and INR (HR 1.446) were found to be risk factors of survival. Conclusion. AFP could be a useful marker to predict outcomes of acute-on-chronic liver failure.